Rasio Keuangan dan Harga Saham Perusahaan Manufaktur - Adhitanaya, Komang; Diviariesty, Kadek (E-Jurnal Akuntansi; Vol 33 No 11 (2023)DO - 10.24843/EJA.2023.v33.i11.p18, 2023)
Improving the welfare of company owners is the company's main goal. In making efforts to improve the welfare of owners, companies increase share prices which are a reflection of the company's value. The aim of conducting research is to empirically test the influence of CR, ROA, ROE, NPM and TATO on share prices of manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (BEI) in the 2018-2021 period. Purposive sampling was used as a technique for determining the research sample. The estimation method for this research is multiple linear regression analysis. This research finds that ROA has a positive effect on stock prices, while ROE and NPM have a negative effect on stock prices. This research also found that CR and TATO had no effect on stock prices. This research has a contribution in providing supporting evidence regarding signaling theory. Keywords: Financial Ratio; Stock Price